2018
DOI: 10.1182/blood-2018-200
|View full text |Cite
|
Sign up to set email alerts
|

Thrombopoietin Receptor Agonists for Severe Thrombocytopenia after Allogeneic Stem Cell Transplantation: Experience of a Multicenter Study from the Grupo Español De Trasplante Hematopoyético (GETH)

Abstract: Introduction Thrombocytopenia is a common complication after allogeneic hematopoietic stem cell transplantation (allo-SCT). Underlying mechanisms are poorly known and usually multifactorial. Its treatment is not well defined, mostly based in platelet transfusion. Thus, is important to identify new strategies to manage this important post-SCT complication. Romiplostim and Eltrombopag are currently available thrombopoietin receptor agonists (TPO-RAs) that stimulate platelet production. Some studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…71 Platelet transfusions remain the backbone of therapy, while boost doses of CD34 þ cells have been used in PGF. 68 Some retrospective studies, as seen in ►Table 2, examined TPO-RA's role in this context, with reported response rates varying from 39.3 to 83.3%, [72][73][74][75][76][77][78][79][80][81][82][83] whereas results from few prospective studies are mostly conflicting. 84,85 Both ROMI and EP, and recently avatrombopag, proved to be as safe and effective and possibly cost-effective in comparison to transfusions in thrombocytopenia after allo-HSCT and PGF.…”
Section: Thrombopoietin Receptor Agonists In Allogeneic Hematopoietic...mentioning
confidence: 99%
See 1 more Smart Citation
“…71 Platelet transfusions remain the backbone of therapy, while boost doses of CD34 þ cells have been used in PGF. 68 Some retrospective studies, as seen in ►Table 2, examined TPO-RA's role in this context, with reported response rates varying from 39.3 to 83.3%, [72][73][74][75][76][77][78][79][80][81][82][83] whereas results from few prospective studies are mostly conflicting. 84,85 Both ROMI and EP, and recently avatrombopag, proved to be as safe and effective and possibly cost-effective in comparison to transfusions in thrombocytopenia after allo-HSCT and PGF.…”
Section: Thrombopoietin Receptor Agonists In Allogeneic Hematopoietic...mentioning
confidence: 99%
“…84,85 Both ROMI and EP, and recently avatrombopag, proved to be as safe and effective and possibly cost-effective in comparison to transfusions in thrombocytopenia after allo-HSCT and PGF. 69,[72][73][74][75][76][77][78][79][80][81][82][83][84] Notably, EP can elicit multilineage responses and along with its immunomodulatory and anti-inflammatory effects can induce enhancement of impaired hematopoiesis in allo-HSCT patients with PGF. 69,74,75,[78][79][80][81] EPinduced iron chelation is also beneficial in these patients, which are characterized by high ferritin levels and iron overload, since iron decrease could result in BM microenvironment reconstitution.…”
Section: Thrombopoietin Receptor Agonists In Allogeneic Hematopoietic...mentioning
confidence: 99%
“…У больных после алло-ТГСК, получавших элтромбопаг, частота общего ответа превысила 60 %. Во время лечения примерно у 15 % пациентов развились изменения функции печени (повышение трансаминаз более чем в 2,5 раза или уровень билирубина был в 2 раза выше нормы), но ни один больной не прекра тил лечение из-за побочных эффектов или неперено симости [52][53][54]. Ромиплостим одобрен для лечения рефрактерной хронической ИТП.…”
Section: российский журналunclassified